2018
DOI: 10.1126/science.aas9466
|View full text |Cite
|
Sign up to set email alerts
|

Activation mechanism of a human SK-calmodulin channel complex elucidated by cryo-EM structures

Abstract: Small-conductance Ca2+-activated K+ (SK) channels mediate neuron excitability and are associated with synaptic transmission and plasticity. They also regulate immune responses and the size of blood cells. Activation of SK channels requires calmodulin (CaM), but how CaM binds and opens SK channels has been unclear. Here we report cryo-electron microscopy (cryo-EM) structures of a human SK4-CaM channel complex in closed and activated states at 3.4- and 3.5-angstrom resolution, respectively. Four CaM molecules bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
242
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(249 citation statements)
references
References 78 publications
7
242
0
Order By: Relevance
“…Moreover,t he radiationless deactivation rates are drastically higher for the latter and significantly enhanced for 19 and 20,ifcompared with 16-18.This is surprising since [16][17][18] have additional side chains providing extra degrees of freedom and therefore ah igher density of rotovibrational states that could favor non-radiative relaxation pathways.T his points to radiationless transitions that are mostly governed by electronic effects associated to the variable substitution patterns.T he latter is evident for 19-20 but particularly for 15,ascan be also observed in the more polar CH 2 Cl 2 /CH 3 OH mixture in which all cases the radiative relaxation rates are (modified accordingto literature [13] ). slightly slower than in CH 3 CN while the radiationless processes are somewhat faster than in the less polar environment (Table 3).…”
Section: Synthesis Of the Probesmentioning
confidence: 98%
“…Moreover,t he radiationless deactivation rates are drastically higher for the latter and significantly enhanced for 19 and 20,ifcompared with 16-18.This is surprising since [16][17][18] have additional side chains providing extra degrees of freedom and therefore ah igher density of rotovibrational states that could favor non-radiative relaxation pathways.T his points to radiationless transitions that are mostly governed by electronic effects associated to the variable substitution patterns.T he latter is evident for 19-20 but particularly for 15,ascan be also observed in the more polar CH 2 Cl 2 /CH 3 OH mixture in which all cases the radiative relaxation rates are (modified accordingto literature [13] ). slightly slower than in CH 3 CN while the radiationless processes are somewhat faster than in the less polar environment (Table 3).…”
Section: Synthesis Of the Probesmentioning
confidence: 98%
“…EF-hands are found within the cytoplasmic regions of these channel proteins and alter channel function upon localized calcium accumulation. In contrast, the small conductance Ca 2+ activated K+ channel, SK (Lee and MacKinnon, 2018) and the subfamily of KCNQ voltage-gated K + channels, Kv7.4 (Chang et al, 2018) forms a complex with Ca 2+ binding protein, CaM, which regulates Ca 2+ dependent activation.…”
Section: Discussionmentioning
confidence: 99%
“…The channel lacks a voltage sensor domain and is therefore not voltage dependent, an important feature that allows the channel to evoke a robust hyperpolarisation response when the cell is activated, during which time the membrane potential approaches −80 mV, the equilibrium potential of K + (Grgic, Kaistha, Hoyer, & Kohler, ). Recently, Lee and Mackinnon et al () have examined the structure of K Ca 3.1 in closed and activated states via cryogenic electron microscopy, providing significant insight into the gating mechanisms of K Ca 3.1 (Lee & Mackinnon, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cryogenic electron microscopy has shown that in the absence of Ca 2+ , the K Ca 3.1 channel pore remains closed by maintaining the resting state. Specifically, CaM stays associated with the channel through its C‐lobe, while the CaM N‐lobe maintains only weak interactions with the channel and is conformationally flexible (Lee & MacKinnon, ). When there is an increase in Ca 2+ concentration, the CaM N‐lobe binds to Ca 2+ triggering a conformational change, increasing the affinity of the N‐lobe for the S 45 A helix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation